2005
DOI: 10.1158/1055-9965.epi-05-0013
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Genetic Variants of Genes of the Hemochromatosis Pathway and Their Role in Breast Cancer

Abstract: Iron overload has been noticed as a feature of human breast cancer. Cellular iron uptake is regulated by the hemochromatosis and transferrin receptor system, mutations of which cause the iron storage disease hereditary hemochromatosis. To understand the role of hemochromatosis and transferrin receptor system mutations in breast cancer, we analyzed 19 sequence variations at HFE, TFR1, TFR2, and FPN1 and compared genotype frequencies between cases and controls in a German population. There were 688 breast cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 27 publications
0
32
1
Order By: Relevance
“…Primarily, GENICA aimed to investigate gene-environment interactions (29)(30)(31) and contributes to the International Breast Cancer Association Consortium (32,33). When the first epidemiological results for night work as a potential risk factor for breast cancer were emerging, we added questions on shift work to our study.…”
Section: Discussionmentioning
confidence: 99%
“…Primarily, GENICA aimed to investigate gene-environment interactions (29)(30)(31) and contributes to the International Breast Cancer Association Consortium (32,33). When the first epidemiological results for night work as a potential risk factor for breast cancer were emerging, we added questions on shift work to our study.…”
Section: Discussionmentioning
confidence: 99%
“…Heterozygous HFE carriership is associated with moderately increased iron parameters, and therefore, it has been suggested to be a genetic modifier of several clonal disorders (solid tumors and hematologic malignancies). Previous association studies regarding common HFE genetic variants in relation with susceptibility for solid tumors such as colon cancer (7,8,(14)(15)(16)(17), or breast cancer (9)(10)(11)18), are rather conflicting. HFE associations were investigated in hematologic malignancies as well.…”
Section: Discussionmentioning
confidence: 99%
“…The S142G variant of TFR was reported to influence cancer susceptibility (colon, breast, myeloma) in combination with distinct HFE genotypes (13). The effects of iron homeostasis, and HFE and TFR genotypes were extensively studied in several solid tumors even in large patient cohorts (7)(8)(9)(10)(11)(12)(14)(15)(16)(17)(18)), but only a few studies with small patient cohorts tested the potential role of HFE in chronic myeloproliferative disorders (CMPD), a clonal disorder of the main iron using tissue of the body (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Kallianpur and others (68) concluded that HFE Tyr282 allele was more frequent in a group of cases with breast cancer from Tennessee in comparison with women from the same state or the general population (P < 0.001). These observations may be explained by the elevated cellular iron uptake associated with the HFE Tyr282 allele (69) or the high iron content in breast cancer cells (61). However, these observations are limited to a low number of patients (61,68).…”
Section: Breast Cancermentioning
confidence: 99%
“…These observations may be explained by the elevated cellular iron uptake associated with the HFE Tyr282 allele (69) or the high iron content in breast cancer cells (61). However, these observations are limited to a low number of patients (61,68).…”
Section: Breast Cancermentioning
confidence: 99%